New records of aphid species (Hemiptera: Aphididae) in Greece - Papapanagiotou, A. P.; Nathanailidou, M.; Taylor, M.; Zarpas, K. D.; Voudouris, K.; Tsitsipis, J. A.; Margaritopoulos, J. T. (ENTOMOLOGIA HELLENICA, 2012)
Several papers have been published on aphid fauna in Greece during the last two decades, but the number of recorded species is still low compared to other European countries, including some from the Mediterranean basin. In this context, we collected aphids from various host-plants and regions in southern, central and northern Greece characterized by diverse flora, climatic conditions and ecological habitats. In total, 128 aphid species belonging to 55 genera and six subfamilies were collected on 200 host-species. Most of the species dominated the subfamily Aphidinae (especially tribes Macrosiphini and Aphidini). Among the species collected, 18 were new records in Greece. The present work improves our knowledge regarding the aphid fauna of Greece and suggests that the number of recorded species could increase further if additional studies were undertaken.